Odpowiedź :
a) 4x(3-y)+½(3-y)= 12x-4xy+1,5-½y
b) (2x-1)+11(2x-1)=2x-1+22x-11= 24x-12
c) -6(½x+y)-(-20)(½x+y)=-3x-6y-10x-20y= -13x-26y
d) -¾x(y+5)-(y+5)=-¾xy-3¼x-y+5
Pozdrawiam ;)
Dałaś dość mało punktów mogę najlepszą? ;)
b) (2x-1)+11(2x-1)=2x-1+22x-11= 24x-12
c) -6(½x+y)-(-20)(½x+y)=-3x-6y-10x-20y= -13x-26y
d) -¾x(y+5)-(y+5)=-¾xy-3¼x-y+5
Pozdrawiam ;)
Dałaś dość mało punktów mogę najlepszą? ;)
a) 4x(3-y)+½(3-y)= 12x-4xy+1,5-½y
b) (2x-1)+11(2x-1)=2x-1+22x-11= 24x-12
c) -6(½x+y)-(-20)(½x+y)=-3x-6y-10x-20y= -13x-26y
d) -¾x(y+5)-(y+5)=-¾xy-3¼x-y+5
Mysle ze pomoglem tez to w szkole mam :D
b) (2x-1)+11(2x-1)=2x-1+22x-11= 24x-12
c) -6(½x+y)-(-20)(½x+y)=-3x-6y-10x-20y= -13x-26y
d) -¾x(y+5)-(y+5)=-¾xy-3¼x-y+5
Mysle ze pomoglem tez to w szkole mam :D
a) 4x(3-y)+1\2(3-y)= 12x -4y +1.5 -0.5y = 12x +1.5 -4.5y
b) (2x-1)+11(2x-1)=2x-1+22x-11= 24x-12
c) -6(1\2x+y)-(-20)(1\2x+y)=-3x-6y -12x-20y= -15x-26y
d) -3\4x(y+5)-(y+5)= -0.75y +3.75 -y-5 = -1.75y -1.35
b) (2x-1)+11(2x-1)=2x-1+22x-11= 24x-12
c) -6(1\2x+y)-(-20)(1\2x+y)=-3x-6y -12x-20y= -15x-26y
d) -3\4x(y+5)-(y+5)= -0.75y +3.75 -y-5 = -1.75y -1.35